Policy Evaluation of the Complete Systematic Land Registration (PTSL) Program in Mamasa Regency - zakaria; Andi Kasmawati; Herman H; Andi Anugrah Mahyuddin; Nur Fadilah Guntur (International Journal Of Public Policy and Bureaucracy, 2025)
This study evaluates the implementation of the Complete Systematic Land Registration Program (PTSL) in Mamasa Regency through six dimensions of policy performance: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Using a qualitative evaluative approach supported by document analysis and field observations, the findings reveal that the program is effective, achieving 98% of the land measurement target, full completion of land parcel mapping (PBT), and issuance of 17,902 land certificates. Efficiency is reflected in optimal time management and sufficient human resources, despite reliance on temporary staff (PPNPN). However, adequacy remains a challenge due to low registration rates and unresolved issues of overlapping maps and ownership disputes. The program demonstrates equity by reaching underserved groups, including farmers and remote communities, through accessible services and direct village outreach. Responsiveness is evident in the active engagement of the Land Office through counseling and community dialogues, which were met with high public enthusiasm. The accuracy dimension is fulfilled through compliance with legal and technical guidelines and responsiveness to community needs for land tenure security. Supporting factors include strong government backing, adequate human resources, and inter-agency collaboration. In contrast, inhibiting factors such as budget constraints, limited infrastructure, adverse weather, lack of land documentation, and unverified ownership in certain areas continue to hinder optimal implementation. These findings highlight the need for structural improvements in land administration policy, particularly in data verification and institutional coordination, to ensure sustainable land governance.